Implementation of the Al-Iktisyaf Book Memorization Method to Improve Vocabulary Mastery Among Students at Nurur Rohman Islamic Boarding School Jember - Jannah, Mawaddatul; Aziz, Abdul; Ifawati, Nur Ila; Qomariyah, Via Nuril; Al Azmi, Fadilah (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2025)
Arabic is one of the important languages ​​learned for spiritual, educational, and communicative purposes. One of the main challenges in learning Arabic is mastering the vocabulary, which is the foundation for understanding and using the language. This study aims to explore the implementation of the al-iktisyaf book memorization method to improve vocabulary mastery among students at nurur rohman islamic boarding school. This study uses a descriptive qualitative approach with primary data obtained through observation, interviews with teachers, students, and Islamic boarding school administrators, as well as secondary data from books, journals, and related documentation. The results of the study indicate that the Al-Iktisyaf Book memorization method, which includes the technique of memorizing nash, nadhom, and the rules of nahwu sharraf, significantly improves the mastery of the students' vocabulary. The memorization process is carried out with flexible time, where students submit their memorization to the teacher individually. Supporting factors for the success of this method include motivation from the teacher through praise and support, memorization repetition strategies, and routine evaluation. In addition, this method is supported by initial learning using the bandongan method which provides basic understanding to students before they memorize. This study concludes that the application of the Al-Iktisyaf Book memorization method at the Nurur Rohman Jember Islamic Boarding School is effective in enriching vocabulary and improving students' Arabic language skills. This is indicated by the increasing ability of students to remember and use new vocabulary in the context of vocabulary in the context of learning the Al-Iktisyaf book. With this method, students not only expand their vocabulary but also improve their ability to read and understand Arabic texts, which supports holistic mastery of language skills.